Quantitative artifact reduction and pharmacologic paralysis improve detection of EEG epileptiform activity in critically ill patients. (January 2023) - Kulick-Soper, Catherine V.; Shinohara, Russell T.; Ellis, Colin A.; Ganguly, Taneeta M.; Raghupathi, Ramya; Pathmanathan, Jay S.; Conrad, Erin C.
Highlights: Pharmacologic paralysis improves detection of EEG epileptiform activity regardless of type of movement-related artifact present. Artifact reduction improves detection of EEG epileptiform activity as much as pharmacologic paralysis when primary source of artifact is EMG. In the appropriate setting, both artifact reduction and paralysis facilitate identification of epileptiform activity in critically ill patients. Abstract: Objective: Epileptiform activity is common in critically ill patients, but movement-related artifacts—including electromyography (EMG) and myoclonus—can obscure EEG, limiting detection of epileptiform activity. We sought to determine the ability of pharmacologic paralysis and quantitative artifact reduction (AR) to improve epileptiform discharge detection. Methods: Retrospective analysis of patients who underwent continuous EEG monitoring with pharmacologic paralysis. Four reviewers read each patient's EEG pre- and post- both paralysis and AR, and indicated the presence of epileptiform discharges. We compared the interrater reliability (IRR) of identifying discharges at baseline, post-AR, and post-paralysis, and compared the performance of AR and paralysis according to artifact type. Results: IRR of identifying epileptiform discharges at baseline was slight ( N = 30; κ = 0.10) with a trend toward increase post-AR (κ = 0.26, p = 0.053) and a significant increase post-paralysis (κ = 0.51, p = 0.001). AR was as effective as paralysis at improving IRR of identifying discharges in those with high EMG artifact ( N = 15; post-AR κ = 0.63, p = 0.009; post-paralysis κ = 0.62, p = 0.006) but not with primarily myoclonus artifact ( N = 15). Conclusions: Paralysis improves detection of epileptiform activity in critically ill patients when movement-related artifact obscures EEG features. AR improves detection as much as paralysis when EMG artifact is high, but is ineffective when the primary source of artifact is myoclonus. Significance: In the appropriate setting, both AR and paralysis facilitate identification of epileptiform activity in critically ill patients.